Teacher readiness in applying ATL skills in the International Baccalaureate Middle Years Programme Schools - Roziah Ramli; Mohd Isha Awang; Nurahimah Mohd Yusoff (Institute of Advanced Engineering and Science, 2021)
This article aims to understand the challenges faced by teachers in implementing the Approaches to Learning Skills (ATL Skills) for the teaching of Bahasa Melayu (Malay Language) in the International Baccalaureate Middle Years Programme Schools (MYPIB) in Malaysia. This qualitative case study employed purposive sampling that involved six resilient teachers who were directly involved in the implementations of ATL Skills consisting of four Bahasa Melayu teachers, a MYPIB coordinator and ATL skills coordinator. Triangulation was used to compare data from different sources using semi-structured interviews, story completion tasks, and document analysis. Using the ATLAS.ti software as an aiding tool, thematic analysis was carried out to identify the themes that emerged from the codes. Findings showed that teacher readiness is a challenge that needs to be addressed in the process of applying ATL skills in the MYPIB implemented by the Malaysian Ministry of Education. Teachers still need courses and training to improve their mastery in the ATL skills application. This study provided implications to teaching and learning, and recommendations to teachers as well as the Ministry to make improvements in the effort to apply ATL skills in the teaching-learning processes at the MYPIB schools.